Neural Circuitry of Impulsivity in a Cigarette Craving Paradigm - Bourque, Josiane; Mendrek, Adrianna; Dinh-Williams, Laurence; Potvin, Stephane (Frontiers in Psychiatry, 2013)
Impulsivity has been shown to play a pivotal role in the onset, pattern of consumption, relapse and, most notably, craving of illicit and licit drugs such as cigarette smoking. The goal of this study was to examine the neurobiological influence of trait impulsivity during cue-induced cigarette craving. Thirty-one chronic smokers passively viewed appetitive smoking-related and neutral images while being scanned and reported their feelings of craving. They completed the Barratt Impulsiveness Scale, a measure of trait impulsivity. We conducted functional connectivity analyses using the psycho-physiological interaction method. During the processing of smoking stimuli, participants presented increased activations in the cingulate and prefrontal cortices, as well as in the limbic system. We observed a significant positive relationship between impulsivity scores and reported craving. A negative correlation was observed between the impulsivity score and activity in the posterior cingulate cortex (PCC). The insula, dorsal anterior cingulate cortex (dACC) as well as the dorsolateral prefrontal cortex (DLPFC) presented a negative connectivity with the PCC. Consistent with the view that the PCC is related to the ability to resist cigarette craving, our results suggest that high impulsive smokers have greater difficulty in controlling their cravings, and that this weakness may be mediated by lower PCC activity. Moreover, we argue that the less PCC activity, the greater the probability of a stronger emotional, physiological and biased attentional response to smoking cues mediated by insula, dACC and DLPFC activity. This is the first study on this topic, and so, results will need to be replicated in both licit and illicit drug abusers. Our findings also highlight a need for more emphasis on the PCC in drug addiction research, as it is one of the most consistently activated regions in fMRI studies examining the neural correlates of cue-induced alcohol, drug and tobacco cravings.